EASE OF WEB DESIGN USING MACROMEDIA DREAMWEAVER 4.0 VERSION - Machmud S (Jurnal Sistem Informasi, 2002)
Web designing is a skill that requires much art and support the appropriate software.The main success of designing a web page is the software used, in other words if thesoftware provides an easy and also the advantage of providing any special facilities tomake or design a website page that are focused on the beauty aspect. Although manyWeb authoring software is emerging but with the 4.0 version of MacromediaDreamweaver software makes us easy to design or design a web page that is reallygood in terms of beauty and design of the Web.Given this personal website, the author can provide an information on how to designa web page with ease which is provided as well as existing advantages in the softwareso that the benefit to our site visitors and a website designer.